Sistem Nominalisasi Bahasa Gayo: Kajian Struktur dan Semantik - Zainuddin, Zainuddin (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016, 2016)
This article deals with the system of nominalization in Gayo language. It is aimed at investigating the procces of morphology in terms of affixation based on the two different stems: adjective and verb in Gayo language. Semantically this is to find out the grammatical meaning carried out by the procces of affixation. The method of reaserch applied qualitative and descriptive by natural approach developed by (Seliger and Elana: 1989) and (Muhadjir:1989). The object of the reaserch is nominalization in Gayo language. The sources of the data used the text books which written in Gayo language as well as using informants of Gayo native speakers. Based on the analysis of the data, the findings showing that the procces of affixation in the system of nominalization in Gayo language based on the stems adjective and Verb. Based on the adjective stem the highest frequency is an affix { ke-en } (34.30%) . In other words, it is the most productive one, and infix { -in- } the lowest one (0.25%) . Based on the verb stem the highest frequency is an affix { pen-en } ( 13.68% ). While the lowest one is the one affix { we- } ( 0.23% ). Therefore the grammatical meanings resuling from the procces of the affixation for nominalization in Gayo language tend to be varities. There are, 8 types of affixes and 17 types of grammatical meanings which based on the adjective stem. While in verb stem there are 7 types of affixes and 12 types of grammatical meanings. And semantically, there are 11 types of grammatical meanings.
Keywords: System, Nominalization Gayo language